2015
DOI: 10.1111/jgh.12841
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic fat, not visceral fat, is associated with gallbladder polyps: A study of 2643 healthy subjects

Abstract: Fatty liver, an ectopic regional fat deposit, was found to be closely associated with GBPs independent of known metabolic risk factors, insulin resistance, and CT-measured VAT, confirming a relevant clinical relationship between the two diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
2
14
1
1
Order By: Relevance
“…Additionally, BMI was an independent risk factor for cholesterol polyps, which is consistent with previous research [7]. Previous studies have found that the formation of GBP is closely related to the overweight status of patients [18][19][20]. Thus, weight control may help reduce the risk of cholesterol polyp formation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, BMI was an independent risk factor for cholesterol polyps, which is consistent with previous research [7]. Previous studies have found that the formation of GBP is closely related to the overweight status of patients [18][19][20]. Thus, weight control may help reduce the risk of cholesterol polyp formation.…”
Section: Discussionsupporting
confidence: 90%
“…Liver function status has a certain influence on the formation of cholesterol polyps. The specific mechanism of the relationship between the two is unclear, and poor liver function may be related to symptoms of hypermetabolic syndrome, including obesity, hyperglycemia, hyperlipidemia, and hypertension [18]. Lipid metabolism, together with abnormal liver function, may interact closely and simultaneously contribute to the formation of cholesterol polyps.…”
Section: Discussionmentioning
confidence: 99%
“…The speci c mechanism of the relationship between liver function status and cholesterol polyps is unclear, and the poor liver function may be related to hypermetabolic syndrome, including obesity, hyperglycemia, hyperlipidemia and hypertension. [18] Lipid metabolism, together with abnormal liver function, may interacts closely and simultaneously contribute to the formation of cholesterol polyps. The mechanisms need to be further discussed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Previous studies found that the formation of GBP was closely related to overweight status of patients. [18][19][20] Thus, weight control may help reduce the risk of cholesterol polyps formation. We suspect that both liver function metabolism and BMI may be related to abnormal lipid metabolism, which, of course, need further studies to con rm.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting results about the relationship between GBP and obesity; some studies found that increasing BMI or obesity status is associated with GBP, while Cantürk et al Conducted a study on 432 patients and found that patients with GBP were not severely obese(BMI > 30) [ 8 , 20 , 21 ]. However, it seems that most studies agree with the formation of GBP being associated with fat metabolism [ 21 23 ]. In this study, in univariate analysis, no strong and direct association was found between BMI and GBP ( P = 0.10); however, based on pathway analysis, high BMI is one of the important predictors which contribute to GBP through increasing the TG level pathway.…”
Section: Discussionmentioning
confidence: 99%